Feeding the future: the critical role of seeds in food systems and cultural heritage - Guedes, Marta; Ferreiro, Maria de Fátima (9th conference on localized agri-food systems, 2022)
Genetic resources constitute a critical resource to deal with the current climatic and geostrategic challenges. The XXI century reintroduced the problem of food security in political and scientific agendas of developed countries. At the roots of this re-emergence are multidimensional reasons: economic (cereals crisis in 2008), public health (covid pandemic), and war (Russia vs Ukraine). Within this context, the reflection on basic issues concerning the food system, namely food production and the resources involved in, such as seeds, is of utmost importance. The paper presents an exploratory approach to genetic conservation through banks in Portugal. The sections of the paper include a problematization, namely the international and national framework on the subject, the design of an analytical model, and the presentation of the results of a case study of a Portuguese genetic bank.